Identifikasi Listeria monocytogenes pada Susu Kambing di Kabupaten Purworejo Jawa Tengah - Monika Danaparamitha Andriani; Trioso Purnawarman; Retno Damayanti; Syafril Daulay (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2016)
Listeria monocytogenes is a pathogenic Listeria species, especially for high-risk groups and it that can be transmitted through contaminated food. Goat milk produced by traditional milking process and storage has a high risk of contamination. The aim of this study was to identify the presence of L. monocytogenes in fresh goat milk in Puworejo regency, Central Java. This study used 60 samples of raw goat milk that were obtained from seven farms by disease detection sampling method. All of the used method in this research refer to Indonesian National Standard (SNI) ISO 11290-1: 2012 about Microbiology of food and feed for detection and enumeration of Listeria monocytogenes. A total of 60 samples of raw goat milk that used in this study were not contaminatedwith L. monocytogenes. Based on the results of this study, it can be concluded that all the samples of raw goat milk were free from L. monocytogenes and have fulfilled the Indonesian National Standard (SNI) ISO No. 7388: 2009 about Limit of Microbial Contamination in Food.